2017
DOI: 10.1126/science.aaj9384
|View full text |Cite
|
Sign up to set email alerts
|

Dengue diversity across spatial and temporal scales: Local structure and the effect of host population size

Abstract: A fundamental mystery for dengue and other infectious pathogens is how observed patterns of cases relate to actual chains of individual transmission events. These pathways are intimately tied to how strains interact and compete across spatial scales. Phylogeographic methods have been used to characterize pathogen dispersal at global and regional scales, but have yielded few insights into the local spatio-temporal structure of endemic transmission. Using geolocated genotype (N=800) and serotype (N=17,291) data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
170
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(196 citation statements)
references
References 41 publications
17
170
1
Order By: Relevance
“…This provides strong support of our modeling framework by suggesting that the model can correctly identify spatio-temporal clustering of otherwise undetected infections. These findings also support focal transmission, irrespective of disease outcome 13,30,31 . The approach presented here will be applicable across disease systems where longitudinal titer data exists, allowing a wide range of insights into fundamental questions of disease ecology and risk.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…This provides strong support of our modeling framework by suggesting that the model can correctly identify spatio-temporal clustering of otherwise undetected infections. These findings also support focal transmission, irrespective of disease outcome 13,30,31 . The approach presented here will be applicable across disease systems where longitudinal titer data exists, allowing a wide range of insights into fundamental questions of disease ecology and risk.…”
supporting
confidence: 68%
“…These findings are consistent with a reduced risk of disease from DENV-4 compared to other serotypes resulting in a largely silent DENV-4 epidemic. This is supported by a phylogenetic analysis that found DENV-4 was widespread in Thailand throughout this period (Figure S4 in Salje et al , 13 ). This suggests the serotype distributions from hospital-based or community-based surveillance may not be representative of infections in the population and supports previous evidence that the transmissibility of a serotype can be delinked from the propensity to cause symptomatic and/or severe disease 14,15 .…”
supporting
confidence: 55%
“…Vero passage-2 stocks, following the original isolation in C6/36 cells, were used for infection of NHP and mosquitoes. The stocks were sequenced using DENV1 and DENV2 specific primers, respectively, on the Illumina MiSeq platform as described in [78] to authenticate contents. The genomes were assembled using an in-house developed reference mapping pipeline, ngs_mapper (https://github.com/ VDBWRAIR/ngs_mapper).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Differential selection pressures exerted by the complex interplay of distinct virus factors, such as infection efficiency, population density and herd immunity (Plowright et al, 2017;Salazar et al, 2010). For example, a recent study reported by Salje et al (2017) demonstrated the association between population density and the establishment of transmission chains. The increase in mosquito populations has also been identified as a potential determinant of the emergence and increased transmission of arbovirus, particularly in immunologically naïve human populations (Dudas et al, 2018;Pettersson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%